Transformasi Digital dan Perbaikan Mutu: Program Pendampingan Inovasi Teknologi, Layanan, dan Proses pada UMKM Kuliner di Bandar Lampung - Ayu Nursari; Hamida Nur Rahmawati; Eka Octa Seprina Ramadhan; Della Ayu Cahyani; Youlanda Tri Mareta (Jurnal Penelitian dan Pengabdian Masyarakat, 2025)
The rapid development of digital technology has significantly transformed the operations of micro, small, and medium enterprises (MSMEs), particularly in the highly competitive culinary sector. This Community Service Program aims to enhance innovation capacity and competitiveness among culinary MSMEs in Bandar Lampung City through digital transformation and quality improvement of products and services. The program was implemented through participatory mentoring, including needs assessment, training on simple digital technologies (such as online marketing, application-based ordering systems, and digital financial management), and guidance on product and service innovation. The results show increased understanding and application of innovation and digitalization among MSME partners. Overall, this program contributes to strengthening the competitiveness of local culinary MSMEs through adaptive innovation management aligned with technological advancement and modern market needs.